Atomic Magnetometer Achieves Visual Salience Analysis in Drosophila - Fan Liu; Dongmei Li; Yixiao Li; Zhao Xiang; Yuhai Chen; Zhenyuan Xu; Qiang Lin; Yi Ruan (Sensors, 2023)
An atomic magnetometer (AM) was used to non-invasively detect the tiny magnetic field generated by the brain of a single Drosophila. Combined with a visual stimulus system, the AM was used to study the relationship between visual salience and oscillatory activity of the Drosophila brain by analyzing changes in the magnetic field. Oscillatory activity of Drosophila in the 1–20 Hz frequency band was measured with a sensitivity of 20 fT/<semantics><msqrt>Hz</msqrt></semantics>. The field in the 20–30 Hz band under periodic light stimulation was used to explore the correlation between short-term memory and visual salience. Our method opens a new path to a more flexible method for the investigation of brain activity in Drosophila and other small insects.